Effectiveness of l-arginine/l-lysine in retarding deterioration of structural and gelling properties of duck meat myofibrillar protein during freeze-thaw cycles. (February 2023) - Li, Mengmeng; He, Shufeng; Sun, Yangying; Pan, Daodong; Zhou, Changyu; He, Jun
Abstract: This study aimed to investigate the protective effects of l -arginine (L-arg) and l -lysine (L-lys) on the structure and gel properties of myofibrillar protein (MP) in duck meat during several freeze- thaw (F- T) cycles. The analysis of the Ca 2+ -ATPase activity as well as total sulfhydryl and carbonyl contents demonstrated that L-arg and L-lys could slow down the oxidative denaturation of MP during F-T cycles. Circular dichroism, fluorescence spectroscopy, and rheology measurements indicated that L-arg and L-lys improved the stability of the secondary and tertiary structure of MP and preserved its gel properties. In summary, L-arg and L-lys had the potential to preserve the structural stability and gel properties of MP during F-T cycles. Graphical abstract: Image 1 Highlights: Freeze-thaw (F-T) cycles impaired stability/gel properties of duck myofibrillar protein (MP). l -arginine reduced the rate of increase in carbonyl content of MP during F-T cycles. During F-T cycles, l -arginine reduced the loss of Ca 2+ -ATPase activity and inhibited the oxidation of sulfhydryl. l -arginine preserved MP structural stability and gel properties during F-T cycles.